(untitled) (Research, Society and Development, 2021)
The structure of a plant community is important for understanding the forest ecosystem, ensuring its sustainable use. The objective of this work was to characterize the Park’s plant composition and losses inherent to these types due to anthropic changes. The study area is located in Belém, with 44.06 ha in length. The caculated parameters were the importance value index, natural regereneration, size category, sociological position and expanded importance value. In areas A1 and A2, there was a balance in the values of VIFs for the most important families Clusiaceae, Arecaceae and Fabaceae. It is important to highlight, in Area A3, the families Arecaceae, Fabaceae, Clusiaceae and Caesalpiniaceae. Caraipa grandiflora and Mauritia carana presented higher values of IVIr% in the evaluated areas. Species that gained importance were those that obtained higher values of sociological position and natural regeneration and those that lost, even having representatives in the middle and upper strata, did not show natural regeneration.